Main features of a Monetary and Credit Policy (Вестник КазНУ. Серия Экономическая, 2017)
Analysis of the instruments of the monetary and credit policy is presentedin the article. Central banks use these instruments for the purposesof monetary and credit regulation within the economy in order to providestability, efficiency and growth of the local market. Central banks in theiractivity choose main priorities of the monetary and credit policy aiming toestablish a price stability, an effective level of money supply and circulation,as well as a payment system development. Regulation of the financialsystem and its participants can be considered as an additional task for thecentral banks.From one hand, if the world market have positive movements, instrumentsof the monetary and credit policy issued by the central bank,stimulate and push the economy to the further growth. From other hand,in agressive economic environment, these measures support and protectan internal market from a negative influence arising in present or comingin future.